Science image in Portugal: studying high school students - Ruão, Teresa (2012)
In the development of activities for the dissemination of science and scientific work there are difficulties and challenges. People get in touch with science in different contexts, as in their workplace or their social life. However, it is in school that the largest number of interaction activities occurs, through communication and education practices. And high school is probably a key context to the promotion of science among young people. We have conducted an exploratory study on the image of science within Portuguese high school students, in order to collect useful data for communicating and attracting them to higher education. For this purpose, we have gathered a research team that includes two researchers of Basic Sciences (responsible for bringing to the project their vision and experience on science communication activities over the years) and two researchers of Communication Sciences (in charge of designing the study and its conceptual framework). This interdisciplinary team has been crossing experiences and knowledges gathered from their contact with communication science practices and their research in strategic communication. Within this context, we have developed a pilot survey that analyses the image of science and scientists hold by high school students within University of Minho’s area of influence (north of Portugal).